Linking Personality to Lecturers’ Employability and Affective Commitment - Alifuddin, Moh.; Widodo, Widodo (Jurnal Pendidikan Progresif, 2022)
Linking Personality to Lecturers’ Employability and Affective Commitment. Objectives: This study explores the effect of personality on employability and lecturers’ affective commitment, and how employability mediating personality affects affective commitment. Methods: A questionnaire collected data through the survey methods toward 230 lecturers in Indonesia spread across four provinces: Jakarta, Banten, West Java, and Central Java. Data analysis uses path analysis supported by descriptive statistics and correlational. Finding: The results show that personality had a significant direct effect on affective commitment, employability had a significant direct effect on affective commitment, personality had a significant direct effect on employability, and personality had a significant indirect effect on affective commitment mediated by employability. Conclusion: A new model regarding the effect of personality on lecturers’  affective commitment, mediated by employability, was confirmed. Thus, the researchers and practitioners can adopt or adapt a new empirical model to increase teachers’ affective commitment through personality and employability in the future, various filed and contexts. Keyword: personality, employability, affective commitment, lecturer.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202221